Constabulary Forces and American Hegemony in Central America from a Global Perspective (1898-1930) - Corella Ovares, Esteban (2026)
This paper reflects on the establishment of national guards in Central American countries at the beginning of the 20th century, which were affected by the consolidation of the United States as a global power after its victory in the war against Spain. In this context, the US government embarked on a series of practices aimed at imposing means of control over Central American territories. Although most of the Central American states were not directly occupied by the United States, part of the US policies included the reform of the armed forces of the Central American States, through the construction of constabularias, also known as national guards. The national histories of Central American countries tend to study these processes independently, neglecting the fact that they were nourished by the experience and circulation of ideas that characterized the functioning of imperial entities.